New 3C Silicon Carbide on Silicon Hetero-Junction Solar Cells for UV Collection enhancement. Issue 1693 (23rd June 2014) - Toure, M.; Berenguier, B.; Ottaviani, L.; Pasquinelli, M.; Palais, O.; Di Lauro, P.; Portail, M.; Chenot, S; Wood, T.; Kobor, D.
ABSTRACT: An actual trend to enhance solar cells efficiency is to build multijunction cells, creating a bandshape wavelength collection. However, the best multijuction cells are actually made of III-V compounds when silicon and its alloys don't lead to high efficiency devices. In this article, we study a 3C-SiC/Si heterojunction as a first step for 3C-SiC/Si tandem cells. Four samples were fabricated by depositing 3C-SiC on Si wafers with different SiC doping levels. Simulations of the structures are performed, as well as optical and electrical characterizations of the heterojunction cells.